"Lingua receptiva" czy "lingua franca"? Językowe kontakty polsko-czeskie na pograniczu w kontekście biznesowym = "Lingua receptiva" or "lingua franca"? On Polish-Czech communication in a business context - Steciąg, Magdalena; Woźniak, Jesica (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article concentrates on the issue of communication in the Polish-Czech border area in a business context. The research material are surveys ? based on Roos Berkens` online study of 2010 ? conducted in English among eleven Czech employees of the border company, Rockwool.
Keywords: kontakty językowe; "lingua franca"; "lingua receptiva"; language contacts